Asymmetry of characteristic X-ray peaks obtained by a Si(Li) detector - Visñovezky, Claudia Analía (2007)
The asymmetry of the characteristic X-ray peaks obtained using a Si(Li) detector is mainly due to incomplete charge collection. Impurities and defects in the crystalline structure of Si can act as "traps" for holes and electrons in their trip toward the detector electrodes. Therefore, the collected charge, and consequently the detected energy, is smaller than the expected one. The global effect is that peaks may present a "tail" toward the low energy side. This phenomenon is more important for low energies (lower than 2.3 keV, in the case of the detector characterized). In this work, the parameters related to peak asymmetry were studied, allowing a better understanding of the trapping process mentioned above. For this purpose, spectra from mono- and multi-element samples were collected for elements with atomic number between 7 and 20. In order to describe the shape of the characteristic K peaks as a function of its energy, an asymmetric correction to a Gaussian function was proposed. Spectra were obtained by electron probe microanalysis for incidence energies between 5 and 25 keV using an energy dispersive spectrometer equipped with an ultra-thin window Si(Li) detector. It was observed that the area corresponding to the asymmetric correction exhibits an energy dependence similar to that of the mass absorption coefficient of the detector material. In addition, other two spectrometers were used to investigate the dependence of tailing on the detection system. When two spectrometers with the same kind of detector and different pulse processors were compared, peaks were more asymmetric for lower peaking time values. When two different detectors were used, differences were even more important. © 2007 Elsevier B.V. All rights reserved.